Paroctonchus nanjiensis gen. nov., sp. nov. (Nematoda, Enoplida, Oncholaimidae) from intertidal sediments in the East China Sea - Shi, Benze; Xu, Kuidong (Zootaxa, 2016)
Paroctonchus nanjiensis gen. nov., sp. nov. is described from a sand beach in the China Nanji Islands Natural Reserve in the East China Sea. Paroctonchus nanjiensis is distinct in the family Oncholaimidae in having more than three teeth, a character found otherwise only in the monotypic genera Octonchus and Patagonema. The new genus and species differs from Octonchus and Patagonema in the number and pattern of teeth, bearing three large teeth with the left ventrosublateral one the largest plus about 27 small teeth distributed on the wall of buccal cavity. By contrast, Octonchus possesses one large tooth plus eight small teeth, while Patagonema has three large teeth with the right ventrosublateral one the largest plus 12 small teeth on three mandibular ridges. Moreover, Paroctonchus nanjiensis differs from Octonchus also in position of the amphidial aperture (located in the middle portion of buccal cavity vs. at the base of buccal cavity), and from Patagonema in the absence of a demanian system (vs. present) and the presence of two subventral rows of wart-like precloacal supplements (vs. a ventral row of papillate supplements). We provide an improved diagnosis for the subfamily Octonchinae, and discuss the evolution of teeth in the family Oncholaimidae.